Tell me how and where you play football and I’ll tell you how much you have to run - Castellano, Julen; Errekagorri, Ibai; Los Arcos, Asier; Casamichana, David; Martín-Garcia, Andres; Clemente, Filipe; López-Del Campo, Roberto; Resta, Ricardo; Echeazarra, Ibon (Biology of Sport, 2022)
The aim of thisstudy wasto describe the team accumulated physical response per minute considering only the effective playing time (EPT) attending to different contextual and strategic variables in the Spanish Football First Division (LaLiga Santander). A  sample of 2,959 performances was included in the analysis, considering a 4-year period of analysis (from 2016–17 to 2019–20). The physical variables were: total distance covered with (DTminPOS) and without (DTminNOpos) possession of the ball, and distance covered at > 21 km·h-1 with possession (DT21minPOS) and without (DT21minNOpos). Two contextual variables, i.e. Place (Home/Away) and Score (Lost/ Draw/Win), and two strategic variables, i.e. level of effective playing time (LevelETP) and level of possession of the ball (LevelPOS), were analysed. The teams ran more without possession of the ball than with possession; nevertheless, the teamsthat had less possession of the ball had higher values ​​in the distance covered at > 21 km·h-1 with possession of the ball and vice versa. Furthermore, the strategic variables also had influence on the physical response (DT and DT21) of the teams,LevelETP and LevelPOS, although with interactive effects: longer playing time, less accumulated distance, and greater possession, greater accumulated distance in the defensive phase, both per min. The findings of this study may offer important practical implications to practitioners in order to assess physical performances of the players in matches, because it is crucial to integrate in the analysis the different contextual and strategic variables where the match has taken place to assess performances of the teams.